Aesthetic Principles of Subahnale Songket: A Cultural Product of Sukarara Village (Universitas Negeri Semarang, 2022)
This study explores the aesthetic principles of the Subahnale songket which is one of the ancestral heritages of the Sasak tribe. Employing the qualitative method, data collection was carried out through observation, interviews, and documentation. Data analysis techniques included data collection, data reduction, data presentation, and conclusion drawing. The principles of aesthetics by DeWitt Henry Parker were used for data analysis. The results of this study show that Subahnale songket weaving has various aesthetic motifs. The craftsmen develop motifs and colors to keep up with the times. They introduce new designs while adhering to the standard, which is geometric hexagons. The aesthetic principles in the Subahnale songket is expected to impart knowledge to the younger generation and can serve as a reference for preserving the Subahnale songket weaving.